The physiology and biochemistry of prokaryotes - David White (Oxford University Press, 2000)
Revised and updated throughout, this second edition features new chapters on macromolecular synthesis and the response of bacteria to environmental stress. It also includes new material on cell division and extracellular polysaccharide synthesis and expands the chapter on signaling. The Physiology and Biochemistry of Prokaryotes, 2/e, provides more detail on the diversity of microbial systems and how they work than all similar texts. It can be used in conjunction with a laboratory manual, Microbial Physiology and Biochemistry Laboratory: A Quantitative Approach, coauthored by David White and George D. Hegeman (OUP, 1997)